Efektivitas Muscle Energy Technique dan Static Stretching terhadap Keluhan Myofascial Pain Syndrome Otot Upper Trapezius pada Pekerja Batik Laweyan Surakarta - Ayubi, Mochamad Zulfan; , Arif Pristianto, SSt.FT.,M.Fis (2017)
Background: The development of batik industry in Indonesia is affect to the increase in working time of batik workers. The workers have to work for 8 hours per day with one hour break time in 6 days / week, with a static and non-ergonomic position for long periods, so can cause musculoskeletal disorders. It is commonly cause neck pain or Myofacial Pain Syndrome in Upper trapezius muscle. Interventions were considered effective to reduce complaints is stretching exercises, such as Muscle Energy Technique and Static Stretching. It is necessary for research to compare the effectiveness of two interventions. Research Aims: To determine the comparative effectiveness of interventions Muscle Energy Technique and Static Stretching to complaints Myofacial Pain Syndrome Upper trapezius muscle on Laweyan Surakarta batik workers. Method: This was a quantitative research with pre-experimental design, using pre-test and post-test two group design. Use purposive technique sampling. The total sample of 20 people. Result: Based on tests of influence with Paired t-test on a group of Muscle Energy Technique with a p-value = 0.000 means that there is the effect of a decrease in pain and improvement of ROM, and test the effect Paired t-test on a group of Static Stretching with a p-value = 0.000, which means there's decrease effect in pain and improvement of ROM. Test the difference between groups to know different influences used Independent t-test p-value = 0.000 thus concluded there's difference effect between Muscle Energy Technique and Static Stretching. Conclusion: There are differences in the effectiveness of Muscle Energy Technique and Static Stretching for Myofacial Pain Syndrome of Upper trapezius muscle on batik workers at Laweyan Surakarta.